The comparison of the basic thinking skills in private and government kindergartens"Studying of the third category of children in Jableh city" (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to know the level basic thinking skills for kindergarten children (third category)  in private and government kindergartens children, and to know the difference between children in the basic thinking according to the type of kindergarten variable. And to know the difference between the gvernment kindergarten children in the basic thinking according to the variable of gender, and to know the difference between the private kindergarten children in the basic thinking according to the variable of gender. And to achieve that follow the descriptive approach. and the basic thinking skills test was prepared, and it's validity and reliability were confirmed, and the sample of the research was included (120) child from the children of the third category in jableh city, (70) child from the private kindergarten children, and (50) child From the government kindergarten children, the results showed that:                                                                                                        • The level of the basic thinking skills each of private and government kindergartens children (third category) was average.• There is a difference among kindergarten children (third category) in the basic thinking skills according to the variable type of the kindergarten in favor of private kindergarten children.• There is no difference among private kindergarten children (third category) in the level of basic thinking skills according to the variable of gender.• There is no difference among government kindergarten children (third category) in the level of basic thinking skills according to the variable of gender.The research aimed to conduct more research aimed at investigating the level of basic thinking skills of kindergarten children in other categories (the first and the second category).